Associations of Multimorbid Medical Conditions and Health-Related Quality of Life Among Older African American Men. (27th June 2017) - Clay, Olivio J; Perkins, Martinique; Wallace, Gail; Crowe, Michael; Sawyer, Patricia; Brown, Cynthia J
Abstract: Background: African American (AA) men battling multiple morbidities are tasked with managing the components of each condition and are at greater risk for adverse outcomes such as poor health-related quality of life (QOL), disability, and higher mortality rates. Method: Baseline data for AA men from the University of Alabama at Birmingham Study of Aging were utilized. Factor analysis was used to categorize medical conditions and create factor scores. Covariate-adjusted regression models assessed the relationships between categories of conditions and physical and mental health-related QOL as assessed by the SF-12. Results: The mean age of the sample of 247 AA men was 75.36 years and 49% lived in rural areas. Medical conditions fit into three factors: metabolic syndrome, kidney failure and neurological complications, and COPD and heart disease. Covariate-adjusted models revealed that low education, higher levels of income difficulty, and higher scores on metabolic syndrome and COPD and heart disease factors were associated with lower scores on physical health-related QOL, p 's < .05. Higher levels of income difficulty were also associated with lower scores on mental health-related QOL. Discussion: These findings suggest the importance of examining clusters of comorbid medical conditions and their relationships to outcomes within older African American men.